Periphery of a Genocide: Finland and the Holocaust - Silvennoinen, Oula (Holocaust and genocide studies, 2023)
By scrutinizing Finland’s complex position as an Axis ally during the Second World War, this article explores the degree to which the country contributed to the destruction of European Jews. Though historians within Finland continue to debate these issues, the author argues that neither exculpation, nor exclusion from the general framework of Holocaust history are tenable historical approaches. While the extent to which Finland willingly participated in the mass murder of the Jews and other perceived enemies remains an unresolved question, this article reveals how key individuals and lower-level authorities nevertheless knowingly contributed to lethal practices and outcomes. Thus, this article challenges current interpretations of Finland’s involvement in the Holocaust.